Convívio e presença como dramaturgia: a dimensão da materialidade e do encontro nas criações da Companhia Brasileira de Teatro - Luciana Eastwood Romagnolli (2013)
The objective of this dissertation is to discuss the articulations of presence and conviviality as elements of dramaturgy considering a context in which they gain prominence in the contemporary theater scene by exploiting the ontological specificity of theatre as strategies to find its place and political potential in the contemporary world. Based on a review of the concepts of presence, conviviality and dramaturgy, this dissertation conceives dramaturgy not only as the articulation of senses but as much as the articulation of various effects produced and involved in the structure of a work and, therefore, the production of presence as a crucial component in dramaturgical thinking of a strand of contemporary Brazilian theatre. This perspective adopted aligns with Gumbrechts (2011) investigations on the production of presence; Dubattis (2007) investigations about conviviality, and Turner and Behrndts (2008) investigations on the dramaturgy as process that implies connection, assembling and structuring elements and effects to compose a work. Gumbrechts ideas about what meaning cannot convey are congruent with Richard Schechners (2003) and Diana Taylors (2003) defense of performance as a knowledge separated from the discursive field. Under the light of the research developed by Erika Fischer-Lichte (2012), which classifies presence in a weak, a strong and a radical concepts and relate them to the emergence of the embodied mind, this research dwells upon the work of the Companhia Brasileira de Teatro, proposing an analysis of their performances, especially Vida, by taking the dimension of presence and conviviality as structural dramaturgy.